(untitled) (The Insight, 2024)
Introduction: The selection of anesthesia for cesarean section is determined by numerous factors, including the indication for operative delivery, its urgency, and patient and obstetrician preference and skill of anesthetists. Spinal opioid therapy is one option for managing pain following surgery. Objective: The aim of this paper was to compare and determine the efficacy of intrathecal fentanyl with different doses of bupivacaine on caesarean patients attended in a tertiary care hospital. Methods: This cross-sectional comparative study was carried out at the department of Anesthesiology and ICU in Kurmitola General Hospital (KGH), Dhaka, Bangladesh during December, 2023 to May, 2024. A total of 60 pregnant caesarean cases aged (18-40) years were enrolled in this study. The pregnant caesarean cases were divided into three groups with 20 cases in each group Subarachnoid block with 0.5% hyperbaric bupivacaine 10 mg and fentanyl 25 μg was administered to patients in Group A. Subarachnoid block with 0.5% hyperbaric bupivacaine (12.5 mg) and fentanyl (25 μg) was administered to patients in Group B. Subarachnoid block with 0.5% hyperbaric bupivacaine (15 mg) and fentanyl (25 μg) was administered to patients in Group C. With the aid of the Statistical Package for Social Sciences, the collected data were examined (SPSS). Unpaired t tests were performed to compare the groups mean where p<0.05 considered as the level of significance. Results: Effective analgesia duration (the interval between the start of sufficient analgesia and the initial request for analgesia) was 115.00±19.11 minutes in group A, 126.25±16.29 minutes in group B, and 131.75±10.70 minutes in group C, respectively. Incidence of pruritis was more as compared to other side effects in all the three groups (20%, 30% and 20% respectively). Conclusion: This study investigated that the combination of fentanyl 25µg with 0.5% hyperbaric bupivacaine 15 mg is more useful, acceptable clinically and superior in terms of characteristics of sensory and motor block, duration of analgesia and greater haemodynamic stability as compared to other two combinations.